Функціонально-енергетична система людини як сучасна біофізична реальність - Макац, Д.В.; Макац, В.Г. (Культура народов Причерноморья, 2004)
The unknown before "functional-power system of biological objects is opened (effects Makatsa)". On a plenty of experimental material (8.256 supervisions) its biophysical activity and specific interdependence between separate components is proved. Materials of researches beyond controversy testifies to reality of hypothetical meridians of the Chinese theory of Chgen-Tszyu therapy and direct relation of the open system to the vegetative functional-power equilibrium. Opening puts traditional acupuncture on a material biophysical basis and unites East and Western therapeutic conceptions.